Hyperbaric welding of duplex stainless steel pipelines offshore. - Farrell, J. (Cranfield University, 1996)
Three duplex stainless steels (Avesta 2205, Sandvik SAF2507 and Zeron 100) were successfully welded automatically at a range of pressures from 1 to 32bar. The gas tungsten arc (GTA) welding process was chosen as it allows a high degree of control to be exercised during welding. Initial autogenous bead on plate welds established the effects of pressure on the welding process and allowed the process parameters to be determined for subsequent experiments. Analysis of the effects of pressure on the weld thermal cycle showed that at higher pressures the precipitation of phases deleterious to the weld quality was less likely than at ambient pressure. It was also found that the arc melting efficiency increased as the pressure increased, which was taken into account when the process parameters for the joints were selected. A V-butt design with a "land" on each side was chosen for the joints to counteract any tendency for the welding arc to wander at higher welding pressures. The root welds were performed using pulsed current welding techniques to overcome the difficulties in achieving consistent penetration that were encountered when welding at lower pressures. It was found that by employing standard welding consumables commonly used for welding duplex steels at ambient pressure satisfactory austenite-ferrite phase balances could be achieved in the weld metal at all pressures. Metallographic examination of the welds showed that the joints did not have any microstructural complications that were related to pressure and mechanical testing revealed that, in terms of impact toughness, the weld metal and heat affected zone (HAZ) performed as well as, if not better than, the parent plate material. This work shows that welding of duplex stainless steels using the hyperbaric welding method is a viable option for subsea operations up to a depth of at least 320m, automated hyperbaric welding being advantageous at depths greater than 40m.